Penerapan Data Mining Untuk Prediksi Penerima Bantuan Pangan Non Tunai (BPNT) Di Desa Wanacala Menggunakan Metode Naïve Bayes - Ermanto; Danny, Muhtajuddin (Jurnal SIGMA, 2023)
The Smart Indonesia Card (KIP) College policy was launched by the government under the auspices of the Ministry of Education and Culture (Kemendikbud) through the National Team for the Acceleration of Poverty Reduction (TNP2K). The aim of this program is to help poor students to obtain a decent education, prevent students from dropping out of college, and to fulfill their college needs. It is hoped that this assistance will be used by students to meet college needs such as transportation costs for students to go to college, costs for college equipment, and pocket money. With the Smart Indonesia Card, it is hoped that no more students will drop out of college due to lack of funds. The Smart Indonesia Card (KIP) funds are given to students who are less able to continue their studies. Keywords: Classification, Naïve Bayes, Rapid Miner, Smart Indonesia Card